Penerapan Model Pembelajaran Group Investigation untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa di SMK YPWKS Cilegon - Wildan Arief Firmasyah; Irwanto Irwanto; Desmira Desmira (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This research is a type of Classroom Action Research (CAR) which aims to improve the quality of the teaching and learning process which leads to an increase in student activity and student result in Basic Electrical and Electronics subjects. The design of classroom action in this study refers to the design of Kemmis & Taggart model which consist of several cycles and each cycle there are four stages, namely (1) planning stage, (2) action stage, (3) observation stage, and (4) reflection stage. The population of this study were students of class X TOI in the Industrial Automation Engineering Expertise Program at SMK YPWKS Cilegon, the samples in this study were students of class X TOI A as many as 22 people. Data were collected through tests and observations. Technical analysis of data using descriptive quantitative. The results showed that the application of Group Investigation learning model in Basic Electrical and Electronics subjects could increase the student activity and student result of class X TOI A students. This increase in activity can be seen from student contribution during the learning process in the form of student enthusiasm in paying attention to teacher explanations, paying attention to friends' explanations while presentations, asking question, expressing opinions, taking notes on material, writing assignments given by the teacher, and working together with groups. The highest achievement in the indicator is paying attention to the teacher’s explanation, taking notes and listening to the teacher’s explanation, each indicator has a percentage of 95,45%. Meanwhile, the lowest achievement is the indicator of doing group work and listening to questions and answers with a percentage of 72.73%. The increase in student learning activity has an effect on increasing students' psychomotor and cognitive learning outcomes. The average value of psychomotor learning outcomes in the first cycle was 67.73%, increasing to 81.82% in the second cycle. The students' cognitive aspect obtained the percentage of the first cycle of 74.06% and the second cycle increased to 69.32%. And increased in the second cycle that is equal to 82.27 Keywords: Group Investigation;Learning Activity; learning Outcomes;Basic Electrical and Electronics subjects